Close association of olfactory placode precursors and cranial neural crest cells does not predestine cell mixing - Harden, Maegan V.; Ramialison, Mirana; Wittbrodt, Joachim (Developmental dynamics, 2012)
Vertebrate sensory organs originate from both cranial neural crest cells (CNCCs) and placodes. Previously, we have shown that the olfactory placode (OP) forms from a large field of cells extending caudally...
Gesehen am 13.02.2017